2019
DOI: 10.2478/jbcr-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Refraction in Children with Unilateral and Bilateral Congenital Nasolacrimal Duct Obstruction

Abstract: Summary The study aimed to identify the type of refraction in children with unilateral and bilateral congenital nasolacrimal duct obstruction (CNLDO) who underwent nasolacrimal duct probing. One hundred and twelve children aged 1.8 to 13 years, diagnosed with CNLDO, were included in a retrospective study. All the patients had their visual acuity examined, and their refractive status was evaluated. The refractive errors of both eyes were noted, followed by an appropriate management plan. Of the 112 children, 79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…Bagheri et al evaluated refractive state in children with unilateral CNLDO; they reported that in children aged 4 years and older, the interocular difference between spherical error and spherical equivalent was considerable as compared to children younger than 4 years [83]. Contrary to this, in our study, we found no significant association between the age (in months) of the patients and the interocular difference in sphere, cylinder, and SE of affected and non-affected eyes.…”
Section: Cnldo Anisometropia and Amblyogenic Potentialcontrasting
confidence: 99%
See 1 more Smart Citation
“…Bagheri et al evaluated refractive state in children with unilateral CNLDO; they reported that in children aged 4 years and older, the interocular difference between spherical error and spherical equivalent was considerable as compared to children younger than 4 years [83]. Contrary to this, in our study, we found no significant association between the age (in months) of the patients and the interocular difference in sphere, cylinder, and SE of affected and non-affected eyes.…”
Section: Cnldo Anisometropia and Amblyogenic Potentialcontrasting
confidence: 99%
“…Penetrating keratoplasty, while the classical surgical treatment for other corneal diseases, is not appropriate in keratoglobus patients. Other procedures, such as inlay lamellar keratoplasty and limbus-to-limbus epikeratoplasty, have been attempted with variable results [83][84][85]. Preferably a spectacle correction as this also provides protection from rupture.…”
Section: Frontiers In Ophthalmology and Ocular Imagingmentioning
confidence: 99%